2018
DOI: 10.1111/jfpp.13837
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new calcium‐binding peptide from enzymatic proteolysate of Acetes japonicus

Abstract: A novel calcium‐binding peptide was first identified from Acetes japonicus proteolysate. First, the small shrimp was hydrolyzed using Flavourzyme and four peptide fractions of 10–30 kDa, 3–10 kDa, 1–3 kDa, and <1 kDa were recovered and examined for their calcium‐binding activity. The calcium affinity of <1‐kDa fraction was the highest with 277.96 ± 20.93 mg Ca2+/g protein, which was 1.7‐folds lower than that of casein phosphopeptide (CPP). A calcium‐binding peptide with its sequence of Tyr–Glu–Ile–Pro–Ala–Glu–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…3 that the < 1 kDa peptide fraction possessed the strongest CaBC and IBC of 520.38 ± 25.75 mgCa 2+ /g protein (1.1 times higher than that of casein phosphopeptide), 998.04 ± 30.38 µgFe 2+ /g protein (1.7 times lower than that of Na 2 EDTA), respectively. This study was consistent with the research of Huang G et al (2011a) and Vo TDL et al (2018b) on the < 1 kDa peptide fraction exhibiting the highest calcium a nity. The steric obstacle that decreased the capacity to migrate and chelate target metal ions of long chain peptides led to low metal-chelating activity of large peptides (Intarasirisawat R et al 2012).…”
Section: Ohc and Whcsupporting
confidence: 93%
See 2 more Smart Citations
“…3 that the < 1 kDa peptide fraction possessed the strongest CaBC and IBC of 520.38 ± 25.75 mgCa 2+ /g protein (1.1 times higher than that of casein phosphopeptide), 998.04 ± 30.38 µgFe 2+ /g protein (1.7 times lower than that of Na 2 EDTA), respectively. This study was consistent with the research of Huang G et al (2011a) and Vo TDL et al (2018b) on the < 1 kDa peptide fraction exhibiting the highest calcium a nity. The steric obstacle that decreased the capacity to migrate and chelate target metal ions of long chain peptides led to low metal-chelating activity of large peptides (Intarasirisawat R et al 2012).…”
Section: Ohc and Whcsupporting
confidence: 93%
“…The same method in our previous study was employed to perform the calcium-binding test (Vo TDL et al 2018b). After demineralization using macroporous resin (Amberlite IRC -748I, sodium structure, Acros), hydrolysates with different concentrations up to 500 mg/L were blended with 5 mM CaCl 2 and 20 mM sodium phosphate support (pH 7.8), which was then mixed at 22 o C within 30 minutes.…”
Section: Determination Of Cabcmentioning
confidence: 99%
See 1 more Smart Citation
“…The type of enzyme, length of hydrolysis and ratio of enzyme to substrate all affect the CaBC of the final product, and CaBP can be extracted from various sources of proteins via different types of proteases. For example, a CaBP with the sequence of YEIPAEDL was prepared via the hydrolysis of Japanese hairy shrimp protein extract using flavor enzymes [ 29 ]. Similarly, papain was used to hydrolyze tilapia collagen, and three CaBPs were obtained with the sequences GPAGPHGPVG, FDHIVY and YQEPVIAPKL [ 47 ].…”
Section: Preparation Of Calcium Chelating Peptidesmentioning
confidence: 99%
“…Acetes are rich in protein and minerals (Ca, Fe, P, and Se), with more than 17 essential amino acids, and vitamins and are also a good source of astaxanthin [2]. Vo et al found that the proteolysate of Acetes japonicus, a species of the Acetes genus, contains calcium-binding peptides that can be used as a calcium alternative in the manufacture of calcium supplements [3]. In addition, the ethanolic extract from slated and fermented shrimp was found to exert antiatherosclerotic and anticardiovascular activities by lowering serum cholesterol in vivo.…”
Section: Introductionmentioning
confidence: 99%